ANALISIS KIMIA SEPULUH JENIS BAMBU DARI JAWA TIMUR - Gusmailina Gusmailina; Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Chemical analyses of ten bamboo species from East Java has been conducted. The analyses comprised of the determination of cellulose, lignin, pentosan, ash, extractives and the solubility in one percent of sodium hydroxide. These analyses were commonly conducted to determine basic characteristics and ultimate uses of wood.The analyses showed that the cellulose content ranges from 42.4 - 53.6 percent, lignin from 19.8 - 26.6 percent, and pentosan 17.5 - 21.5 percent. The ash and silica content varies from 1.24 - 3.77 percent and from 0.10 - 1.78 percent, respectively: The solubility in cold water ranges from 4.5 - 9.9 percent, in hot water from 5.3 - 11.8 percent, in alcohol benzene ( 1 :2) from 0.9 - 6.9 percent, and in one percent sodium hydroxide solution from 22.2 - 29.8 percent.Based on chemical analyses, especially the cellulose content, the bamboos from East Java appeared to be a good material for pulp and paper industry.